5.3.62 Problems 6101 to 6200

Table 5.407: Second order ode

#

ODE

Mathematica

Maple

18586

\[ {}y^{\prime \prime }+4 y^{\prime }-y = \sin \left (t \right ) \]

18587

\[ {}y^{\prime \prime }+3 y = \sin \left (x \right )+\frac {\sin \left (3 x \right )}{3} \]

18595

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+y = \frac {1}{x} \]

18596

\[ {}y^{\prime \prime } = c \left (1+{y^{\prime }}^{2}\right ) \]

18597

\[ {}y^{\prime \prime } = c \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} \]

18599

\[ {}y^{\prime \prime } = -m^{2} y \]

18600

\[ {}1+{y^{\prime }}^{2}+\frac {m y^{\prime \prime }}{\sqrt {1+{y^{\prime }}^{2}}} = 0 \]

18602

\[ {}x y^{\prime \prime }+2 y^{\prime } = x y \]

18606

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+5 y = \frac {1}{x} \]

18607

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = 2 \,{\mathrm e}^{2 x} \]

18608

\[ {}v^{\prime \prime }+\frac {2 v^{\prime }}{r} = 0 \]

18609

\[ {}y^{\prime \prime }-2 y y^{\prime } = 0 \]

18610

\[ {}y^{\prime \prime }-{y^{\prime }}^{2}-y {y^{\prime }}^{3} = 0 \]

18611

\[ {}\left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} = r y^{\prime \prime } \]

18613

\[ {}\left (1+y^{2}\right ) y^{\prime \prime }-2 y {y^{\prime }}^{2}-2 \left (1+y^{2}\right ) y^{\prime } = y^{2} \left (1+y^{2}\right ) \]

18615

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = 0 \]

18616

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime } = 0 \]

18618

\[ {}v^{\prime \prime }+\frac {2 x v^{\prime }}{x^{2}+1}+\frac {v}{\left (x^{2}+1\right )^{2}} = 0 \]

18655

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

18656

\[ {}y^{\prime \prime }+2 y^{\prime }-2 y = 0 \]

18664

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = 2 \,{\mathrm e}^{2 x} \]

18666

\[ {}y^{\prime \prime }-4 y^{\prime }+2 y = x \]

18667

\[ {}y^{\prime \prime }+3 y^{\prime }-y = {\mathrm e}^{x} \]

18670

\[ {}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{x} \]

18671

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x \]

18672

\[ {}y^{\prime \prime }+y = \cos \left (x \right ) \]

18674

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

18678

\[ {}e y^{\prime \prime } = \frac {P \left (\frac {L}{2}-x \right )}{2} \]

18679

\[ {}e y^{\prime \prime } = \frac {w \left (\frac {L^{2}}{4}-x^{2}\right )}{2} \]

18680

\[ {}e y^{\prime \prime } = -\frac {\left (w L +P \right ) x}{2}-\frac {w \,x^{2}}{2} \]

18681

\[ {}e y^{\prime \prime } = -P \left (L -x \right ) \]

18682

\[ {}e y^{\prime \prime } = -P L +\left (w L +P \right ) x -\frac {w \left (L^{2}+x^{2}\right )}{2} \]

18683

\[ {}e y^{\prime \prime } = P \left (-y+a \right ) \]

18685

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }-8 y = x \]

18689

\[ {}x y^{\prime \prime }+2 y^{\prime } = 2 x \]

18690

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = \ln \left (x \right ) \]

18691

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = 2 x \]

18692

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = x \]

18693

\[ {}y^{\prime \prime }-\cot \left (x \right ) y^{\prime }+\csc \left (x \right )^{2} y = \cos \left (x \right ) \]

18694

\[ {}\left (x^{2}-x \right ) y^{\prime \prime }+\left (3 x -2\right ) y^{\prime }+y = 0 \]

18695

\[ {}\left (3 x^{2}+x \right ) y^{\prime \prime }+2 \left (6 x +1\right ) y^{\prime }+6 y = \sin \left (x \right ) \]

18698

\[ {}y^{\prime \prime } = \cos \left (x \right ) \]

18699

\[ {}x^{2} y^{\prime \prime } = \ln \left (x \right ) \]

18700

\[ {}y^{\prime \prime } = -a^{2} y \]

18701

\[ {}y^{\prime \prime } = \frac {1}{y^{2}} \]

18702

\[ {}y y^{\prime \prime }-{y^{\prime }}^{2} = 0 \]

18703

\[ {}y y^{\prime \prime }-{y^{\prime }}^{2} = 1 \]

18704

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-1-{y^{\prime }}^{2} = 0 \]

18705

\[ {}x y^{\prime \prime }+3 y^{\prime } = 3 x \]

18706

\[ {}x = y^{\prime \prime }+y^{\prime } \]

18709

\[ {}V^{\prime \prime }+\frac {2 V^{\prime }}{r} = 0 \]

18710

\[ {}V^{\prime \prime }+\frac {V^{\prime }}{r} = 0 \]

18724

\[ {}y^{\prime \prime }-\frac {2 y^{\prime }}{x}+\frac {2 y}{x^{2}} = 0 \]

18725

\[ {}v^{\prime \prime }+\frac {2 v^{\prime }}{r} = 0 \]

18726

\[ {}y^{\prime \prime }-k^{2} y = 0 \]

18867

\[ {}y^{\prime \prime }+3 y^{\prime }-54 y = 0 \]

18868

\[ {}y^{\prime \prime }-m^{2} y = 0 \]

18869

\[ {}2 y^{\prime \prime }+5 y^{\prime }-12 y = 0 \]

18870

\[ {}9 y^{\prime \prime }+18 y^{\prime }-16 y = 0 \]

18873

\[ {}y^{\prime \prime }+8 y^{\prime }+25 y = 0 \]

18876

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = {\mathrm e}^{4 x} \]

18877

\[ {}y^{\prime \prime }-y = 2+5 x \]

18878

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 2 \,{\mathrm e}^{2 x} \]

18882

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 3 \,{\mathrm e}^{\frac {5 x}{2}} \]

18886

\[ {}y^{\prime \prime }+a^{2} y = \cos \left (a x \right ) \]

18887

\[ {}y^{\prime \prime }-4 y = 2 \sin \left (\frac {x}{2}\right ) \]

18890

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \sin \left (x \right ) {\mathrm e}^{2 x} \]

18891

\[ {}y^{\prime \prime }+2 y = x^{2} {\mathrm e}^{3 x}+{\mathrm e}^{x} \cos \left (2 x \right ) \]

18892

\[ {}y^{\prime \prime }+4 y = x \sin \left (x \right ) \]

18893

\[ {}y^{\prime \prime }-y = x^{2} \cos \left (x \right ) \]

18897

\[ {}y^{\prime \prime }+4 y = \sin \left (3 x \right )+{\mathrm e}^{x}+x^{2} \]

18898

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x +{\mathrm e}^{m x} \]

18899

\[ {}y^{\prime \prime }-a^{2} y = {\mathrm e}^{a x}+{\mathrm e}^{n x} \]

18905

\[ {}y^{\prime \prime }+a^{2} y = \sec \left (a x \right ) \]

18906

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x^{2} {\mathrm e}^{3 x} \]

18907

\[ {}y^{\prime \prime }+n^{2} y = {\mathrm e}^{x} x^{4} \]

18911

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (2 x \right ) \]

18913

\[ {}y^{\prime \prime }-2 y^{\prime }+4 y = {\mathrm e}^{x} \cos \left (x \right ) \]

18917

\[ {}y^{\prime \prime }-y = x \sin \left (x \right )+\left (x^{2}+1\right ) {\mathrm e}^{x} \]

18918

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = {\mathrm e}^{x} \cos \left (2 x \right )+\cos \left (3 x \right ) \]

18920

\[ {}y^{\prime \prime }-9 y^{\prime }+20 y = 20 x \]

18923

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 2 \ln \left (x \right ) \]

18924

\[ {}x^{2} y^{\prime \prime }+y = 3 x^{2} \]

18927

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }-4 y = x^{4} \]

18928

\[ {}x^{2} y^{\prime \prime }+5 x y^{\prime }+4 y = x^{4} \]

18929

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-20 y = \left (1+x \right )^{2} \]

18930

\[ {}x^{2} y^{\prime \prime }+7 x y^{\prime }+5 y = x^{5} \]

18931

\[ {}\left (2 x +5\right )^{2} y^{\prime \prime }-6 \left (5-2 x \right ) y^{\prime }+8 y = 0 \]

18932

\[ {}\left (2 x -1\right )^{3} y^{\prime \prime }+\left (2 x -1\right ) y^{\prime }-2 y = 0 \]

18934

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = {\mathrm e}^{x} \]

18936

\[ {}\left (x +a \right )^{2} y^{\prime \prime }-4 \left (x +a \right ) y^{\prime }+6 y = x \]

18940

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = x^{m} \]

18941

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = x^{m} \]

18944

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+y = \frac {1}{\left (1-x \right )^{2}} \]

18945

\[ {}x^{2} y^{\prime \prime }-\left (2 m -1\right ) x y^{\prime }+\left (m^{2}+n^{2}\right ) y = n^{2} x^{m} \ln \left (x \right ) \]

18946

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+y = \frac {\ln \left (x \right ) \sin \left (\ln \left (x \right )\right )+1}{x} \]

18948

\[ {}x^{5} y^{\prime \prime }+3 x^{3} y^{\prime }+\left (3-6 x \right ) x^{2} y = x^{4}+2 x -5 \]

18949

\[ {}x y^{\prime \prime }+2 x y^{\prime }+2 y = 0 \]

18950

\[ {}y^{\prime \prime }+2 \,{\mathrm e}^{x} y^{\prime }+2 y \,{\mathrm e}^{x} = x^{2} \]

18951

\[ {}\sqrt {x}\, y^{\prime \prime }+2 x y^{\prime }+3 y = x \]